INOVASI PENGURANGAN SAMPAH PERKOTAAN DALAM MEWUJUDKAN SUSTAINABLE DEVELOMPMENT GOALS DI INDONESIA. - Setiawan, Irfan; Datupalinge, Bangkit Ayatullah; handayani, nur (Institut Pemerintahan Dalam Negeri (IPDN), 2023)
The waste problem in Indonesia is a problem that has not been resolved to date. Waste is the result of human activity that is not reused. One of the human activities that causes the generation of paper waste is the activities of running government offices. Based on this, this article aims to examine alternative urban waste reduction innovations in realizing Sustainable Development Goals in Indonesia. This research uses a literature review method. Information and data obtained from various literature are compiled based on the information obtained and make it relevant to the topic being discussed. The research results found that one of the human activities that produces paper waste is government office activities. Government office activities are one aspect that participates in producing paper waste, and this is a phenomenon that needs to be considered critically. An innovative alternative proposed by the author to help overcome this problem is the use of the Green Newspaper concept in designing the basic materials for paper production. This paper concept can help the use of the Green Newspaper concept to realize one of the Sustainable Development Goals (SDGS) points, namely responsible consumption and production, where paper can be used to minimize waste from the government administration process.